A novel film calibration method, applied to stereotactic cone commissioning - Florin Rosca (International Journal of Radiology and Radiation Oncology - Peertechz Publications, 2019)
Purpose: To present a fi lm calibration technique that uses a few stereotactic cone irradiations on a single strip of fi lm to generate the cone's dose profi le, and its application to the commissioning of stereotactic cones in radiation oncology.